The biblical commission's document "The interpretation of the Bible in the church" text and commentary - Fitzmyer, Joseph A. 1920-2016 (Subsidia biblica, 1995)
"Under date of April 15, 1993, the Pontifical Biblical Commission published in French a document on the interpretation and use of the Bible in the Church. The English translation of the original French document, "The Interpretation of the Bible in the Church", appeared on November 18, 1993. The purpose of the document is "to indicate the paths most appropriate for arriving at an interpretation of the Bible as faithful as possible to its character both human and divine". The English translation of the document is published in its entirety in the present volume, together with a clarificatory commentary by Fr. Joseph A. Fitzmyer, S.J., a member of the Biblical Commission. A detailed bibliography is included. Also published are English translations of the address of His Holiness Pope John Paul II on the occasion of the publication of the French original on April 15, 1993, and of the preface to the document by Cardinal Joseph Ratzinger, President of the Biblical Commission."--BOOK JACKET.